2019
DOI: 10.1186/s13000-019-0852-y
|View full text |Cite
|
Sign up to set email alerts
|

Primary endocervical gastric-type adenocarcinoma: a clinicopathologic and immunohistochemical analysis of 23 cases

Abstract: Background Endocervical gastric-type adenocarcinoma (GAS) is a rare non-human papillomavirus-associated adenocarcinoma (NHPVA) with morphologic and immunohistochemical features of gastric differentiation. This study aimed to evaluate cytologic and clinicopathological features, differential diagnosis of endocervical GAS. Methods A total of 23 patients diagnosed with endocervical GAS/minimal deviation adenocarcinoma (MDA) at Peking University People’s Hospital between 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 20 publications
1
33
1
Order By: Relevance
“…In addition, Omori et al [28] state that “it is difficult to recognize yellow mucin on LBC because the mucin color becomes paler.” In their report, Omori et al [28] nicely illustrate the difference in mucin color (yellow vs. pink in normal endocervix) in an image which also demonstrates the relatively uniform enlargement of the nuclei compared to the normal endocervical cells. Lu et al [15] report that golden-yellow intracytoplasmic mucin was not noticeable in their series of 11 patients with pretreatment Pap tests (both TP and SP) out of a cohort of 23 GAS cases indicating that, indeed, golden-yellow mucin may not be a particularly sensitive feature for GAS detection, at least in LBC. Of note, only 4/11 Pap tests in their study were originally reported as AGC (favor neoplasia or NOS) while the remaining results were NILM, HSIL, and unsatisfactory, thus underlining the difficulty of GAS detection in cytology [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Omori et al [28] state that “it is difficult to recognize yellow mucin on LBC because the mucin color becomes paler.” In their report, Omori et al [28] nicely illustrate the difference in mucin color (yellow vs. pink in normal endocervix) in an image which also demonstrates the relatively uniform enlargement of the nuclei compared to the normal endocervical cells. Lu et al [15] report that golden-yellow intracytoplasmic mucin was not noticeable in their series of 11 patients with pretreatment Pap tests (both TP and SP) out of a cohort of 23 GAS cases indicating that, indeed, golden-yellow mucin may not be a particularly sensitive feature for GAS detection, at least in LBC. Of note, only 4/11 Pap tests in their study were originally reported as AGC (favor neoplasia or NOS) while the remaining results were NILM, HSIL, and unsatisfactory, thus underlining the difficulty of GAS detection in cytology [15].…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al [15] report that golden-yellow intracytoplasmic mucin was not noticeable in their series of 11 patients with pretreatment Pap tests (both TP and SP) out of a cohort of 23 GAS cases indicating that, indeed, golden-yellow mucin may not be a particularly sensitive feature for GAS detection, at least in LBC. Of note, only 4/11 Pap tests in their study were originally reported as AGC (favor neoplasia or NOS) while the remaining results were NILM, HSIL, and unsatisfactory, thus underlining the difficulty of GAS detection in cytology [15]. Yuan et al [24] note that although golden-yellow mucin was seen, it was relatively scanty in the atypical cells thought to represent gastric-type AIS in their study.…”
Section: Discussionmentioning
confidence: 99%
“…On cervical cytology specimens, GAS has been reported to show endocervical cells in monolayered and honeycomb sheets with well-defined cell borders, pale vacuolar and/or foamy cytoplasm, and vesicular nuclei with conspicuous nucleoli 4,5,7,16,[18][19][20] . Peripheral palisading mimicking feathering has also been reported 18 .…”
Section: Accepted Articlementioning
confidence: 99%
“…Regardless of the histological features, these neoplasms share a non‐HPV related carcinogenesis. Therefore, they are not recognized by primary HPV‐screening, and also surrogate biomarkers of oncogenic HPV‐activity (for example p16) are not useful for the diagnosis of these cancers 1‐3 . Conversely, in non‐screening cytology or in primary cytologic screening settings, NHPVAs may occur.…”
Section: Introductionmentioning
confidence: 99%